Fullerene coated silicon electrodes prepared by a plasma-assisted evaporation technique for the anodes of lithium secondary batteries - Arie, Arenst Andreas; Lee, Joong Kee (KOREAN ASSOC CRYSTAL GROWTH, INC, 2009)
With the aim of enhancing the silicon anode performance in lithium secondary batteries, we have studied the effect of a fullerene thin film as a coating material. The fullerene films were prepared by a plasma assisted evaporation technique from fullerene powder on a Cu foil. As a result, excellent electrochemical performance of fullerene-coated silicon electrodes in terms of stable cycle performance and high specific capacity were observed. The enhanced performances are attributed to the formation of a polymeric phase of the fullerene film as confirmed by Raman spectroscopy, FTIR spectroscopy and XPS analysis. The polymeric layer could act as passive layer to provide mechanical stability against the volume expansion during prolonged cycling tests.